2015
DOI: 10.1021/acschembio.5b00683
|View full text |Cite
|
Sign up to set email alerts
|

The Recognition of Identical Ligands by Unrelated Proteins

Abstract: The binding of drugs and reagents to off-targets is well-known. Whereas many off-targets are related to the primary target by sequence and fold, many ligands bind to unrelated pairs of proteins, and these are harder to anticipate. If the binding site in the off-target can be related to that of the primary target, this challenge resolves into aligning the two pockets. However, other cases are possible: the ligand might interact with entirely different residues and environments in the off-target, or wholly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 73 publications
1
90
0
Order By: Relevance
“…In addition, a large affinity difference is observed between the complexes (BindingDB reports IC 50 values of 0.003–8.3 μM for CAH2 and 164 μM for the chitinase). A similar example was also found by Barelier and colleagues who examined the binding of ligands to unrelated proteins . Comparing the binding modes of AZM in human CAH2 to AZM bound to a highly dissimilar carbonic anhydrase from Coccomyxa sp PA .…”
Section: Methodssupporting
confidence: 66%
“…In addition, a large affinity difference is observed between the complexes (BindingDB reports IC 50 values of 0.003–8.3 μM for CAH2 and 164 μM for the chitinase). A similar example was also found by Barelier and colleagues who examined the binding of ligands to unrelated proteins . Comparing the binding modes of AZM in human CAH2 to AZM bound to a highly dissimilar carbonic anhydrase from Coccomyxa sp PA .…”
Section: Methodssupporting
confidence: 66%
“…By the application of a combined binding energy cutoff, 749 hits remained, which were further reduced to 91 that showed high binding affinity for both EBOV proteins. Recent crystallography analyses also recognised identical ligands for different proteins [57]. The present study revealed a varying trend in docking results obtained against both Ebola viral proteins (VP35 and VP40) of the Zaire strain.…”
Section: Discussionmentioning
confidence: 52%
“…Instead, we prefer to reference recently published crystallographic analyses 75 demonstrating that small molecules may bind multiple proteins in different types of binding sites and with distinct conformations to ultimately facilitate molecular repurposing. While it would be most desirable to repurpose an approved drug and, thus, catapult a discovery effort into a Phase II trial, one should not ignore the significance of utilizing the discovery of a new use for an old drug to seed efforts in the lead optimization phase 76 .…”
Section: Discussionmentioning
confidence: 99%